Nramp1 and NrampB Contribute to Resistance against Francisella in Dictyostelium - Brenz, Yannick; Ohnezeit, Denise; Winther-Larsen, Hanne C.; Hagedorn, Monica (Frontiers in Cellular and Infection Microbiology, 2017)
The Francisella genus comprises highly pathogenic bacteria that can cause fatal disease in their vertebrate and invertebrate hosts including humans. In general, Francisella growth depends on iron availability, hence, iron homeostasis must be tightly regulated during Francisella infection. We used the system of the professional phagocyte Dictyostelium and the fish pathogen F. noatunensis subsp. noatunensis (F.n.n.) to investigate the role of the host cell iron transporters Nramp (natural resistance associated macrophage proteins) during Francisella infection. Like its mammalian orthologue, Dictyostelium Nramp1 transports iron from the phagosome into the cytosol, whereas NrampB is located on the contractile vacuole and controls, together with Nramp1, the cellular iron homeostasis. In Dictyostelium, Nramp1 localized to the F.n.n.-phagosome but disappeared from the compartment dependent on the presence of IglC, an established Francisella virulence factor. In the absence of Nramp transporters the bacteria translocated more efficiently from the phagosome into the host cell cytosol, its replicative niche. Increased escape rates coincided with increased proteolytic activity in bead-containing phagosomes indicating a role of the Nramp transporters for phagosomal maturation. In the nramp mutants, a higher bacterial load was observed in the replicative phase compared to wild-type host cells. Upon bacterial access to the cytosol of wt cells, mRNA levels of bacterial iron uptake factors were transiently upregulated. Decreased iron levels in the nramp mutants were compensated by a prolonged upregulation of the iron scavenging system. These results show that Nramps contribute to host cell immunity against Francisella infection by influencing the translocation efficiency from the phagosome to the cytosol but not by restricting access to nutritional iron in the cytosol.